The Legitimacy of the UN Security Council: Evidence from Recent General Assembly Debates3. Issue 2 (13th May 2014) - Binder, Martin; Heupel, Monika
Abstract : Existing research on the legitimacy of the UN Security Council is conceptual or theoretical, for the most part, as scholars tend to make legitimacy assessments with reference to objective standards. Whether UN member states perceive the Security Council as legitimate or illegitimate has yet to be investigated systematically; nor do we know whether states care primarily about the Council's compliance with its legal mandate, its procedures, or its effectiveness. To address this gap, our article analyzes evaluative statements made by states in UN General Assembly debates on the Security Council, for the period 1991–2009. In making such statements, states confer legitimacy on the Council or withhold legitimacy from it. We conclude the following: First, the Security Council suffers from a legitimacy deficit because negative evaluations of the Council by UN member states far outweigh positive ones. Nevertheless, the Council does not find itself in an intractable legitimacy crisis because it still enjoys a rudimentary degree of legitimacy. Second, the Council's legitimacy deficit results primarily from states' concerns regarding the body's procedural shortcomings. Misgivings as regards shortcomings in performance rank second. Whether or not the Council complies with its legal mandate has failed to attract much attention at all.